Compliance to Gluten-Free Diet May Regenerate Probiotic Microbiota: First Report - Moni Kumari; Malika Arora; Navdeep Kaur; Ranjit Singh; Parveen Bansal (Journal of Integrated Health Sciences)
Background: The human intestinal microbiota is very rich in probiotics which includes various species and strains of Lactobacillus, Bifidobacteria, etc. In certain diseased conditions, friendly microbiota may get disturbed or completely eradicated. To make up the loss of such beneficial species, one has to either replenish it from external source or remove the reasons responsible for killing of the microbiota. Similarly, the intestinal microflora also gets disturbed in celiac disease (CD), an autoimmune disorder caused due to the immune-toxic gluten peptides or due to delivery of variety of antibiotics that may act as dysbiotic agents. Aim: The present study was aimed to investigate the replenishment of microbiota after sticking to gluten free diet in celiac disease patient. Materials and Methods: In this study, ten patients each of four groups were included and their faecal samples were collected. Bacterial colonies were isolated from the sample and the colonies were examined by biochemical and morphological profiling. Results: The biochemical and morphological profile of microbiota in faecal samples demonstrated clear-cut regeneration of probiotic species in patients complying with gluten-free diet (GFD). This is the first report on regeneration of microbiota in relation to dietary compliance in CD patients. Conclusion: The results of study may play a great role in detecting the patient compliance to GFD and may serve as a non-invasive prognostic tool replacing biopsy especially for paediatric population.